Existing data sources in clinical epidemiology: the Scandinavian Thrombosis and Cancer Cohort - Jensvoll, Hilde (Clin Epidemiol, 2015)
BACKGROUND: Although venous thromboembolism (VTE) is a known common complication in cancer patients, there is limited knowledge on patient-related and cancer-specific risk factors in the general population. The Scandinavian Thrombosis and Cancer (STAC) Cohort was established by merging individual data from three large Scandinavian cohorts (The Tromsø Study, the second Nord-Trøndelag Health Study, and the Danish Diet, Cancer and Health Study). Here, we present the profile of the STAC cohort and provide age-specific incidence rates of VTE and cancer. METHODS: The STAC cohort includes 144,952 subjects aged 19–101 years without previous VTE or cancer. Baseline information collected in 1993–1997 included physical examination, self-administered questionnaires, and blood samples. Validated VTE events and cancer diagnoses were registered up to 2007–2012. RESULTS: There were 2,444 VTE events (1.4 per 1,000 person-years [PY]) during follow-up, and the incidence increased exponentially from 0.3 per 1,000 PY in subjects aged 20–29 years to 6.4 per 1,000 PY in subjects aged 80+. Overall, 51% of the VTE events were provoked, and cancer was the most common provoking factor (19%), followed by immobilization and surgery (both 15%). In total, 19,757 subjects developed cancer during follow-up (9.8 per 1,000 PY), and the 5-year age-specific incidence rates of cancer were coherent with corresponding rates from the Norwegian Cancer Registry. CONCLUSION: The STAC cohort will provide a unique opportunity to explore the epidemiology and impact of genetic and environmental patient-related and cancer-specific risk factors for VTE in the general population.